Unforgiving : lessons from the fall - Jacobellis, Lindsey, 1985-; Paisner, Daniel (Harper, an imprint of HarperCollins Publishers, 2023)
In this deeply personal memoir in the vein of Andre Agassi's Open and Megan Rapinoe's One Life , the winningest snowboardcross rider of all time chronicles her career, a story of self-growth that reveals the secret of her resilience and how she overcame crushing early failure to win Olympic gold. On February 16, 2006, twenty-year old American snowboarder Lindsey Jacobellis was poised to win the first gold medal in women's snowboardcross, a sport making its Olympic debut. With a seemingly insurmountable lead over the other competitors, Lindsey only needed a clean run for the gold medal to be hers. But as the five-time world champion entered the last 100 meters the unthinkable choosing to add a little flair to the run, she grabbed the back edge of her board--then lost her balance and fell. It was a mistake that would go down as one of the biggest "unforced errors" in all of sports history. For the next sixteen years, Jacobellis endured the criticism and second-guessing of Olympic commentators, sportswriters, and detractors. Day after day she persevered and trained harder on the snow and with her life coach, learning the power of resilience and what the sport really meant to her. The fierce competitor discovered that life, though it may not seem like it, does happen in just the right you end up precisely where you were meant to be. At the 2022 Beijing Winter Games, Lindsey twice reached the top of the podium, becoming a two-time Olympic gold medalist. Unforgiving recounts Lindsey's journey from disappointment to triumph. It is an honest account of one life-altering misstep and its aftermath, and a reflection on what it means to come of age as an athlete in the spotlight, the weight of expectations, falling short, and ultimately fulfilling your dreams. Unforgiving is about the purpose-driven, forward-looking attitude Lindsey took on after her fall, when looking back wouldn't have done anyone any favors. It's about the pass she refused to grant herself until she'd earned it. Unforgiving is about the commitment to seek her own truth--and to speak up on one's own behalf after letting others do it for years. Forgiveness, in the end, is at the heart of Lindsey's story, but underneath and alongside is its polar opposite--an unending, uncompromising determination to push herself, to prove herself, to power past every obstacle in her path, even those of her own making.